1994
DOI: 10.1161/01.hyp.23.5.565
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular white matter lucency and cerebral blood flow autoregulation in hypertensive patients.

Abstract: The goal of this study was to elucidate the association between the development of periventricular white matter lucency and autoregulation of cerebral blood flow in hypertensive patients through the arteriovenous oxygen saturation difference method. We studied 51 hypertensive patients who had previously suffered from minor strokes (lacunar infarction, 43; deep basal minor hemorrhage, 8). Patients were divided into three groups based on the findings of periventricular white matter lucency. We measured the absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 26 publications
3
113
1
2
Order By: Relevance
“…The fact that our significant correlation was restricted to PV-WMH is consistent with studies on the general population that have related cardiovascular risk factors more consistently to PV-WMH (10,17). On the other hand, other studies of clinical samples have shown that D-WMH may contribute more significantly to the presence of depressive symptoms in patients with stroke (6).…”
Section: Control (N = 14)supporting
confidence: 91%
“…The fact that our significant correlation was restricted to PV-WMH is consistent with studies on the general population that have related cardiovascular risk factors more consistently to PV-WMH (10,17). On the other hand, other studies of clinical samples have shown that D-WMH may contribute more significantly to the presence of depressive symptoms in patients with stroke (6).…”
Section: Control (N = 14)supporting
confidence: 91%
“…Another deleterious vascular effect of A␤ 1-40 is a disruption of cerebrovascular autoregulation (Niwa et al, 2002b), a mechanism in part mediated by vasoactive factors produced in endothelial cells, which prevents fall of CBF during hypotension Jones et al, 1999;Chillon and Baumbach, 2002). Failure of autoregulation leads to ischemic damage of cortical white matter (Matsushita et al, 1994), a finding that may be responsible for the white matter lesions observed in patients with AD (Brun and Englund, 1986;Van Dijk et al, 2004). These observations, collectively, suggest that A␤ peptides, in addition to their well known deleterious effects on neurons (Selkoe and Schenk, 2003), can also disrupt the function of cerebral blood vessels.…”
Section: Discussionmentioning
confidence: 93%
“…4 Once advanced cerebrovascular damage is present, these mechanisms cannot effectively regulate level of cerebral blood flow. 5,6 Therefore, low systemic blood pressure in the presence of cerebrovascular damage may lead to decline in cerebral blood flow, which renders brain tissue vulnerable to ischemic events. 7 Both physical and cognitive impairment are common in very old age and are strongly associated with cerebrovascular pathologies and cerebral hypoperfusion.…”
mentioning
confidence: 99%